Crown‐Ether‐Directed Assembly of One‐Dimensional Silver(I) Coordination Polymers With Dramatically Enhanced Photoluminescence - Xiaojiao Yang; Xiao‐Lin Ye; Shu‐Han Bao; Dong‐Nan Yu; Wenya Jiang; Bintao Wu; Shuaiqi Wang; Kangzhou Wang; Tang Yang; Guozong Yue; Samia Kahlal; Jean‐Yves Saillard; et al. (Aggregate)
ABSTRACT Two novel 18‐crown‐6‐ether (18‐C‐6) directed one‐dimensional silver(I) coordination polymers (1D Ag(I) CPs), formulated as {[(18‐C‐6)Ag(bpy)]·X}∞ and {[(18‐C‐6)Ag(pyz)]·X}∞ {bpy = 4,4′‐bipyridine; pyz = pyrazine; X = BF4− (Ia, IIa), CF3SO3− (Ib, IIb)}, are prepared and structurally determined. The protection of the 18‐C‐6 macrocycle not only efficiently prevents intermolecular interactions within each 1D Ag(I) CP but also significantly enhances the rigidity of the chain structures, allowing these polymers to exhibit remarkable phosphorescence with intense green‐light emission at room temperature. Moreover, IIa and IIb show enhanced photoluminescence quantum yields and aggregation‐induced emission properties, which can be attributed to their close‐packed structure modes in the crystalline states. Interestingly, upon mixing with commercial resin, IIa can serve as an efficient and stable luminescent ink for 3D printing. The resulting printed structures demonstrate exceptional irradiation stability, retaining their luminescence properties without any quenching over a three‐month period. This work not only provides a facile strategy to prepare luminescent 1D Ag(I) CPs but also shows the promise of their utilization in optical devices.